FACTORS AFFECTING AUDIT REPORT LAG ON THE INDONESIA STOCK EXCHANGE (FOR THE PERIODS OF 2019 – 2020) - Fahmil Furqon El Ghofiqiy; Hadri Mulya (Indonesian Journal of Multidisciplinary Science, 2022)
This study aims to analyze the factors that influence audit report lag on the transportation and logistics sector registered in Indonesia stock exchange in the periods 2019 and 2020. The study sample was determined by purposive sampling method. The data used are secondary data from financial statements published by Indonesia stock exchange. The analytical methods used are descriptive statistical analysis and multiple regression statistical analysis. The results showed that going concern opinion was proved to have a significant effect on audit report lag. The tax incentives, public accounting firm size and company size did not affect significantly on audit report lag. The tax incentives did not affect significantly on audit report lag due to companies submitted their financial statement reports on time in order to get tax incentives. Each company that would conduct an auditing would consider to the size of the public accounting firm that would hold auditing of the company. It is also in line with the auditor who will consider the size of the company to be audited so that the auditor can estimate the timeliness of conducting the auditing.